PHYTOCHEMICAL TEST AND ANTIBACTERIAL ACTIVITY OF METHANOL EXTRACT OF MENTAWA LEAF (Artocarpus anisophyllus Mig.) - Pratama, Wahyu; Saleh, Chairul; Astuti, Winni (Jurusan Kimia FMIPA UNMUL, 2020)
Phytochemical test and antibacterial activity of methanol extract of Mentawa leaf (Articarpus anisophyllus Mig.) have been done. The extraction of Mentawa leaf samples was carried out by the maceration method using methanol as a solvent. An antibacterial activity test was carried out using the agar diffusion method. Phytochemical tests results show that methanol extract of Mentawa leaf has secondary metabolites of flavonoid, steroid, triterpenoid, phenolic, and quinone compounds. The antibacterial activity test results obtained MIC values for Salmonella typhi bacteria were 1.25-2.5%, Streptococcus mutans bacteria were 0-0,625%, Streptococcus sobrinus bacteria were 1.25-2.5% and for Propionibacterium acnes bacteria were 0.625-1.25%. Methanol extract of Mentawa leaf has broad-spectrum antibacterial activity.